Measured global thermal performance of a directly irradiated suspension-flow solar particle receiver with an open aperture. (1st January 2022) - Chinnici, A.; Davis, D.; Lau, T.C.W.; Ang, D.; Troiano, M.; Saw, W.L.; Tian, Z.F.; Solimene, R.; Salatino, P.; Nathan, G.J.
Graphical abstract: Highlights: Global performance of windowless vortex-based solar particle receiver measured. Aerodynamic active control implemented to allow open aperture operations. Total heat transfer rate enhanced by the presence of solid phase. Heat absorbed by the fluid higher than that of solid phase. Abstract: We present an experimental investigation of the thermal performance of a 1-kW directly irradiated suspension-flow solar particle receiver with an open (windowless) aperture under simulated solar conditions. Silicon carbide and air were used as the particulate and fluid media, respectively. A 5 kWel xenon-arc solar simulator was used as the energy source. An outlet-suction strategy was employed to induce a net inflow through the aperture as means to mitigate particle and hot fluid egress from the device. The influence of various operating parameters, namely particle loading, air inlet mass flow rate and net air ingress through the aperture on the global thermal performance (thermal efficiency, exergy disruption, specific heat losses and wall temperature distribution) of the device was investigated systematically. It was found that the ratio of the solar input to total heat capacity of the two-phase flow and the level of suction have controlling influence on the global performance of the device. For the operating conditions investigated here, the heat absorbed by the air through the receiver was found to be 3–15 times higher than that of the solid phase, depending primarily on the mass loading and total inlet fluid flow rate. The presence of the solid phase was found to enhance the total heat absorbed by the two-phase flow albeit at the expense of lowering the value of the maximum outlet air temperature.